2009
DOI: 10.1111/j.1365-2036.2009.04000.x
|View full text |Cite
|
Sign up to set email alerts
|

NSAID‐induced antral ulcers are associated with distinct changes in mucosal gene expression

Abstract: SUMMARY BackgroundThe basis for individual variation in gastroduodenal vulnerability to NSAIDs is not well understood.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
4
0

Year Published

2009
2009
2019
2019

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(5 citation statements)
references
References 60 publications
1
4
0
Order By: Relevance
“…This broad antioxidant effect may help to explain the fact that flavocoxid significantly down-regulated COX-2 gene expression in isolated human peripheral blood monocytes from OA patients whereas celecoxib, ibuprofen, and to a minor extent, acetaminophen, augmented COX-2 gene expression ( Figure 4 This was a surprising result since both traditional and selective COX-2 NSAIDs bind to and inhibit the COX enzyme production of inflammatory AA metabolites. Similar results have been found in patients who experience ulcerations in which COX-2 gene expression is up-regulated [90]. While this may be advantageous in maintaining prostaglandin E2 (PGE 2 ) production in the upper GI tract to mitigate ulcer formation, COX-2 gene induction could result in greater protein production generating elevated PG production associated with increased pain and inflammation.…”
Section: Ib Kinasesupporting
confidence: 66%
“…This broad antioxidant effect may help to explain the fact that flavocoxid significantly down-regulated COX-2 gene expression in isolated human peripheral blood monocytes from OA patients whereas celecoxib, ibuprofen, and to a minor extent, acetaminophen, augmented COX-2 gene expression ( Figure 4 This was a surprising result since both traditional and selective COX-2 NSAIDs bind to and inhibit the COX enzyme production of inflammatory AA metabolites. Similar results have been found in patients who experience ulcerations in which COX-2 gene expression is up-regulated [90]. While this may be advantageous in maintaining prostaglandin E2 (PGE 2 ) production in the upper GI tract to mitigate ulcer formation, COX-2 gene induction could result in greater protein production generating elevated PG production associated with increased pain and inflammation.…”
Section: Ib Kinasesupporting
confidence: 66%
“…This is contrary to the situation in humans, where NSAID-induced gastric ulceration occurs mainly in the gastric antrum [31]. For instance, naproxen is the most common and frequent NSAID used in rheumatoid arthritis patients, and the naproxen-induced gastropathy occurs mainly in the gastric antrum [31]. Using this experimental antral model of gastric ulcerations in rats to mimic the human scenario of complication risk after naproxen ingestion, Kim et al [32] have shown that the administration of naproxen caused the macro- and microscopic antral lesions and increased the tissue lipid peroxidation levels.…”
Section: Curcumin-induced Gastric Protection Against Nsaid-inducedmentioning
confidence: 78%
“…These lesions are recognized as bleeding erosions or lesions rather than typical ulcers [28]. This is contrary to the situation in humans, where NSAID-induced gastric ulceration occurs mainly in the gastric antrum [31]. For instance, naproxen is the most common and frequent NSAID used in rheumatoid arthritis patients, and the naproxen-induced gastropathy occurs mainly in the gastric antrum [31].…”
Section: Curcumin-induced Gastric Protection Against Nsaid-inducedmentioning
confidence: 99%
“…It remains controversial whether gastric mucosal atrophy and duodenal metaplasia are reversible or not after eradication of the infection (62) . Furthermore, such possible mucosal alterations are difficult to confirm in consequence of not being possible, in the majority of cases, to obtain data on the previous conditions with respect to the presence of H. pylori in the population included in the studies (20,62) . Anatomopathological studies on peptic ulcers refer signs of inflammation in the regions surrounding the ulcer but not signs of mucosal atrophy (62) .…”
Section: Discussionmentioning
confidence: 99%
“…In order to be sure of the absence of the infectious cause of the peptic ulcer, it is also recommended that samples should be examined from both antrum and corpus, and utilizing two different tests, with negative results for both (62) . A lower bacterial density in the antrum can lead to false-negative urea respiratory tests (1,20,28,36) . It is general to endoscopic procedures that samples be taken from both antrum, where the majority of the ulcers reside, and corpus, where bacterial populations are higher.…”
Section: Discussionmentioning
confidence: 99%